Implementation of Analytic Hierarchy Process Method In the Decision Support System for Selecting Department in University - Syahida Nurhidayarnis; Anisa Putri; Raja Zaid Ibnu Zarier Ismail; Meisya Delila Br Ginting; Walovi Lestari Nurrafa (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
Every year, high school graduates show a strong desire to pursue higher education. However, many of them experience limitations in choosing a Department or study program, creating the